Bacterial pathogens and the autophagic response - Lerena, Maria Cecilia (2010)
The host cell recognition and removal of invading pathogens are crucial for the control of microbial infections. However, several microorganisms have developed mechanisms that allow them to survive and replicate intracellularly. Autophagy is an ubiquitous physiological pathway in eukaryotic cells, which maintains the cellular homeostasis and acts as a cell quality control mechanism to eliminate aged organelles and unnecessary structures. In addition, autophagy has an important role as a housekeeper since cells that have to get rid of invading pathogens use this pathway to assist this eradication. In this review we will summarize some strategies employed by bacterial pathogens to modulate autophagy to their own benefit and, on the other hand, the role of autophagy as a protective process of the host cell. In addition, we will discuss here recent studies that show the association of LC3 to a pathogen-containing compartment without a classical autophagic sequestering process (i.e. formation of a double membrane structure).